Establishment and Optimization of Enhanced Recovery after Surgery System for Lung Cancer - Guowei CHE (Chinese Journal of Lung Cancer, 2017)
With the development of key techniques and programs, the concept of enhanced recovery after surgery (ERAS) has been utilized in a wide range of diseases and surgical specialties. The key technological elements of enhanced lung recovery after surgery (ELRAS), which is regarded as the mainstay of minimally invasive lung cancer surgery, consist of the airway management and the lung protection. A multidisciplinary team cooperation based on physicians, nurses and rehabilitative therapists is needed to achieve the goals of airway management and lung protection, thus establishing a comprehensive ELRAS system for lung cancer patients. Such ELRAS systems should meet the following demands: firstly, there are accurate and objective assessment models for each section in an ELRAS program; secondly, the ELRAS protocols should be made as simple and repeatable as possible; thirdly, there are rigorous evaluation systems for the clinical efficacy of an ELRAS program; finally, a question-oriented team should be constructed in an ELRAS program. In summary, the ELRAS system needs to be constantly optimized and improved in the clinical practices.